UPAYA ADMINISTRATIF TERHADAP KEPUTUSAN DAFTAR PENILAIAN PELAKSANAAN PEKERJAAN (DP3) YANG MERUGIKAN PEGAWAI NEGERI SIPIL DI UNIVERSITAS JENDERAL SOEDIRMAN - Setiajeng Kadarsih; Sutikno Sutikno; Sanyoto Sanyoto (Jurnal Dinamika Hukum, 2013)
Professional development of civil servants through performance assessment is a part of management personnel in the evaluation phase. Normatively, work assessment is made in the form of decisions issued by the officials of the state official. The perceived detrimental decisions of civil servants in the performance appraisal of personnel sometimes been disputed that need a fair settlement. This is what underlies the administrative effort that can be objected and administrative appeals. Keywords: performance appraisal, administrative efforts, employment disputes